2020
DOI: 10.1136/bjophthalmol-2020-317337
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity outcomes and anti-VEGF therapy intensity in macular oedema due to retinal vein occlusion: a real-world analysis of 15 613 patient eyes

Abstract: Background/AimsTo assess visual acuity (VA) outcomes and antivascular endothelial growth factor (anti-VEGF) therapy intensity in retinal vein occlusion (RVO)-related macular oedema (ME).MethodsA retrospective study was completed in treatment-naïve patients with RVO-related ME from 2013 to 2019, using the Vestrum Health Retina Database.ResultsMean baseline age was 72.4 years and 54% were women. In 6 months, in 8876 eyes with branch retinal vein occlusion (BRVO)-related ME, after a mean of 4.5 anti-VEGF injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 27 publications
4
37
1
Order By: Relevance
“…In this multicenter study, we examined the baseline factors of patients with CRVO in Japan, and sought to determine the factors that were significantly associated with the BCVA at the initial examination. The baseline factors of the patients with CRVO were similar to recent real-world data of CRVO: the average age of the patients was about 70 years, and the patients had a higher prevalence of hypertension [13,15,19,26,27].…”
Section: Discussionsupporting
confidence: 75%
“…In this multicenter study, we examined the baseline factors of patients with CRVO in Japan, and sought to determine the factors that were significantly associated with the BCVA at the initial examination. The baseline factors of the patients with CRVO were similar to recent real-world data of CRVO: the average age of the patients was about 70 years, and the patients had a higher prevalence of hypertension [13,15,19,26,27].…”
Section: Discussionsupporting
confidence: 75%
“…The background characteristics of the patients with CRVO were similar to recent real-world data of CRVO: the average age of the patients was about 70 years and patients had a high prevalence of hypertension. 13,15,19,21,22 In our CRVO cohort, there were signi cantly more men (57.3%) than women (42.7%, P<0.001, Table 1). Another recent study of CRVO in Japan also showed that the prevalence was higher in men (64.7%) than women (35.3%), 19 whereas the global epidemiological studies have shown that the prevalence of CRVO did not differ signi cantly between sexes.…”
Section: Discussionmentioning
confidence: 79%
“…Another recent study of CRVO in Japan also showed that the prevalence was higher in men (64.7%) than women (35.3%), 19 whereas the global epidemiological studies have shown that the prevalence of CRVO did not differ signi cantly between sexes. 5,7 Recent real-world reports of CRVO in USA, 15 UK, 21 and Germany 13 also reported almost equal prevalence of CRVO between men and women. We presume that the higher prevalence of CRVO in men may be related to higher prevalence of hypertension and smoking rate of men in Japan.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is estimated that 24.4 million IVT injections were performed globally in 2019 with 6.9 million of these injections performed in the United States, most often for neovascular age-related macular degeneration (nAMD) and diabetic macular edema (DME) [5]. While IVT injections of anti-vascular endothelial growth factor (anti-VEGF) therapies are commonly performed in an office setting, and have demonstrated remarkable therapeutic benefits in controlled clinical trials [6][7][8][9][10][11][12][13][14][15][16][17], real world data on patients receiving IVT injections of anti-VEGF therapies show a much more modest improvement in patients' vision [18][19][20][21][22]. This disparity may relate to treatment burden, with patients undertreated due to an inability to maintain the frequent treatments in fixed regimens utilized in clinical trials.…”
Section: Current Treatment Landscape and Unmet Clinical Needmentioning
confidence: 99%